2005
DOI: 10.1038/ng1516
|View full text |Cite
|
Sign up to set email alerts
|

Brahma links the SWI/SNF chromatin-remodeling complex with MeCP2-dependent transcriptional silencing

Abstract: Transcriptional repression of methylated genes can be mediated by the methyl-CpG binding protein MeCP2. Here we show that human Brahma (Brm), a catalytic component of the SWI/SNF-related chromatin-remodeling complex, associates with MeCP2 in vivo and is functionally linked with repression. We used a number of different molecular approaches and chromatin immunoprecipitation strategies to show a unique cooperation between Brm, BAF57 and MeCP2. We show that Brm and MeCP2 assembly on chromatin occurs on methylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(57 citation statements)
references
References 50 publications
1
54
0
Order By: Relevance
“…MECP2 may also interact with other chromatin-modifying enzymes, such as histone methyltransferases, BRM, SWI/SNF, and ATRX (Fuks et al , 2003; Harikrishnan et al , 2005; Giorgio et al , 2007). Of interest, MECP2 also interacts with the DNA methyltransferase DNMT1, and thus it could be involved in the regulation of DNA methylation (Kimura and Shiota, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…MECP2 may also interact with other chromatin-modifying enzymes, such as histone methyltransferases, BRM, SWI/SNF, and ATRX (Fuks et al , 2003; Harikrishnan et al , 2005; Giorgio et al , 2007). Of interest, MECP2 also interacts with the DNA methyltransferase DNMT1, and thus it could be involved in the regulation of DNA methylation (Kimura and Shiota, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…the Brahma subunit of the SWI/SNF complex [22], [24], [55], TFIIB, CREB1 [15], [56], RNA polymerase II, RNA splicing factor SC35 [57], H3K4 di-methylation and H4K16 acetylation and CpG methylation) ( Table 2 ). While the distribution of most of these factors or epigenetic marks was not altered by targeting MeCP2, we confirmed that MeCP2 targeting interferes with chromatin binding of linker histone H1 (FRAP data not shown), which is compatible with the observed chromatin unfolding [19], [30][32].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Mecp2, the responsible gene of Rett syndrome, negatively related with Fmr1 expression. It is reasonable because Mecp2 plays a role in the transcriptional repression of methylated genes including Fmr1 [20]. However, in TMD-exposed GPIN, Fmr1 was not regulated by RARs, indicating the neural induction by RA was counteracted by TMD.…”
Section: Resultsmentioning
confidence: 99%